Peran Taman Nasional Bromo Tengger Semeru (TNBTS) Resort Wonokitri dalam pengelolaan ekowisata Edelweiss Park Desa Wonokitri Kecamatan Tosari Kabupaten Pasuruan - Denayu Grandis; Nur Hadi; Nanda Harda Pratama Meiji (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The tourism sector is one of the largest foreign exchange earning sectors for a country's economy. The development of the tourism aspect must of course also be balanced with benefits from an economic perspective and cultural integrity for the local community, or better known as Ecotourism. Bromo Tengger Semeru National Park (TNBTS) is one of the administrative areas under the auspices of the Ministry of Environment and Forestry, in which there is an ecotourism-based tourism village development program, namely the Edelweiss Ecotourism Park. The existence of this program cannot be separated from the role of the institutions carried out by the TNBTS so that the tourism management system can still be accountable for the preservation of its resources. The development of a tourist village initiated by TNBTS has a background of problems related to the preservation of Edelweiss flowers in the National Park area by using them for the customary needs of the local community which were previously imbalanced. This research was conducted with the aim of knowing the function of the role of elements of an institution and society in improving the community's economy through ecotourism at Edelweiss Park, Wonokitri Village, Tosari, Pasuruan. The method used in this study is qualitative to produce descriptive data in the form of words or utterances from individuals who are observed, then observed. This study concluded that the ecotourism village development program improved the community’s economy and the knowledge aspect of Edelweiss flower management. Sektor pariwisata menjadi salah satu sektor penyumbang devisa terbesar bagi perekonomian suatu negara. Perkembangan aspek wisata tentunya juga harus diimbangi dengan adanya manfaat dari segi ekonomi serta keutuhan budaya bagi masyarakat setempat, atau yang lebih dikenal dengan istilah Ekowisata. Taman Nasional Bromo Tengger Semeru (TNBTS) menjadi salah satu kawasan wilayah administratif yang dinaungi oleh lembaga Kementrian Lingkungan Hidup dan Kehutanan, yang didalam kawasannya terdapat program pengembangan desa wisata yang berbasis Ekoturisme yakni Ekowisata Edelweiss Park. Adanya program itu juga tidak lepas dari peran lembaga yang dilaksanakan oleh Taman Nasional Bromo Tengger Semeru agar sistem pengelolaan kepariwisataan tetap bisa dipertanggungjawabkan terhadap kelestarian sumberdayanya. Pengembangan desa wisata yang diinisiasi oleh TNBTS mempunyai latar belakang permasalahan yang berkaitan dengan pelestarian bunga Edelweiss dalam kawasan Taman Nasional dengan pemanfaatannya untuk keperluan adat masyarakat setempat yang dahulu belum berimbang. Penelitian ini dilaksanakan dengan tujuan mengetahui fungsi peran elemen suatu lembaga dan masyarakat dalam peningkatan perekonomian masyarakat melalui ekowisata Taman Edelweiss Desa Wonokitri Tosari Pasuruan. Metode yang digunakan dalam penelitian ini yakni kualitatif untuk menghasilkan berupa data deskriptif kata-kata atau ucapan dari individu yang diamati, kemudian diobservasi. Penelitian ini menghasilkan kesimpulan bahwa dari program pengembangan desa ekowisata mampu meningkatkan perekonomian masyarakat serta aspek pengetahuan pengelolaan bunga Edelweiss.